Involvement of Type 1 Angiontensin II Receptor (AT1) in Cardiovascular Changes Induced by Chronic Emotional Stress: Comparison between Homotypic and Heterotypic Stressors - Costa-Ferreira, Willian; Vieira, Jonas O.; Almeida, Jeferson; Gomes-de-Souza, Lucas; Crestani, Carlos C. (Frontiers in Pharmacology, 2016)
Consistent evidence has shown an important role of emotional stress in pathogenesis of cardiovascular diseases. Additionally, studies in animal models have demonstrated that daily exposure to different stressor (heterotypic stressor) evokes more severe changes than those resulting from repeated exposure to the same aversive stimulus (homotypic stressor), possibly due to the habituation process upon repeated exposure to the same stressor. Despite these pieces of evidence, the mechanisms involved in the stress-evoked cardiovascular dysfunction are poorly understood. Therefore, the present study investigated the involvement of angiotensin II (Ang II) acting on the type 1 Ang II receptor (AT1) in the cardiovascular dysfunctions evoked by both homotypic and heterotypic chronic emotional stresses in rats. For this purpose, we compared the effect of the chronic treatment with the AT1 receptor antagonist losartan (30mg/kg/day, p.o.) on the cardiovascular and autonomic changes evoked by the heterotypic stressor chronic variable stress (CVS) and the homotypic stressor repeated restraint stress (RRS). RRS increased the sympathetic tone to the heart and decreased the cardiac parasympathetic activity, whereas CVS decreased the cardiac parasympathetic activity. Additionally, both stressors impaired the baroreflex function. Alterations in the autonomic activity and the baroreflex impairment were inhibited by losartan treatment. Additionally, CVS reduced the body weight and increased the circulating corticosterone; however, these effects were not affected by losartan. In conclusion, these findings indicate the involvement of angiotensin II/AT1 receptors in the autonomic changes evoked by both homotypic and heterotypic chronic stressors. Moreover, the present results provide evidence that the increase in the circulating corticosterone and body weight reduction evoked by heterotypic stressors are independent of AT1 receptors.